Analysis of Factors Affecting Water Environment Quality Based on Flow Analysis. Issue 3 (May 2021) - Zhao, Yichen; Guo, Hongpeng; Qiao, Yang; Ran, Li
Abstract: Taking Tianjin as an example, based on the existing research results, this author improves the framework of urban water flow map and draws a urban water flow map, by using the idea of process, and approaching from the reverse thinking of water environment → discharge (sewage) outlet→sewage treatment→ sewage collection→ water consumption→water supply →water resources. On this basis, the principal component regression method is used to find key factors affecting water environment quality in Tianjin, and provide a decision support for the overall optimization and integrated control of the urban water system.